Religious and prosocial behavior, happiness and its impact on productivity: an evidence from Indonesia - Wiliasih, Ranti; Siregar, Hermanto; Irawan, Tony; SyaukiBeik, Irfan; Hassan, Rusni (BPAS Publications, 2024)
Prosocial is an activity that is carried out consciously to provide benefits to others without expecting a specific reward. Prossociative behavior will increase social finance in society. The purpose of this study is to analyze prosocial behavior and religious behavior on happiness and the impact of happiness on productivity. This study uses primary data from 1121 respondents of independent workers who live in provinces that are included in the average level of happiness based on the 2021 Central Bureau of Statistics Indonesia or Badan Pusat Statistik Indonesia (BPS) survey. Data analysis uses Structure Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results of this study show that prosocial behaviors such as philanthropy, voluntary activities, and religious behaviors such as friendship, gratitude, and tadabbur have a significant positive effect on happiness both in the happiness index with Islamic value and the BPS happiness index. Another important finding of this study is the impact of happiness with both indices on productivity.